Introduction and critical technology analysis of internet of vehicle - Jie LI (Dianxin kexue)
The definition and difference between internet of vehicle and smart car were described.And the development situation of internet of vehicle all over the world was described.The problems and critical technology in the development of internet of vehicle were analyzed.At last，the prospects of internet of vehicle was given under nowadays situation in China.